Trends in pharmacological therapy following an acute coronary syndrome in Portugal: a systematic review. Issue 9 (September 2016) - Pereira, Marta; Lopes-Conceição, Luisa; Bennett, Kathleen; Dias, Paula; Laszczynska, Olga; Lunet, Nuno; Azevedo, Ana
Abstract : Aims: To assess time trends in the use of main drug classes for secondary prevention, during hospitalization and at hospital discharge, following an acute coronary syndrome, in Portugal, using a systematic review. Methods: We searched PubMed, from inception until 2012, to identify studies reporting the proportion of acute coronary syndrome patients treated with main pharmacological therapy. We used linear regression to quantify the annual variation in use of drugs, adjusting for the proportion of men in the sample and patients' mean age, and including a quadratic term of data collection year when relevant. Results: In 25 eligible studies, including patients treated from 1993 to 2009, we observed an increase in the prescription of pharmacological treatments at hospital discharge. Extrapolating from these data, and assuming a mean patient age of 65 years and 70% of men, we estimate that in 2008, 95% of patients would have been discharged with aspirin, 92% with clopidogrel, 82% with β-blockers, 80% with angiotensin-converting enzyme inhibitors and 91% with statins. Treatment during hospitalization followed a similar pattern, except for a steeper increase in angiotensin-converting enzyme inhibitors use, which was initially lower, but reached similar levels to those at discharge in recent years. Conclusion: In Portugal, there was an increase in the use of recommended pharmacological therapy for secondary prevention after an acute coronary syndrome over the last 15 years, during hospitalization and at hospital discharge.